Hepatitis B virus reactivation among hepatitis C patients treated with direct-acting antiviral therapies in routine clinical practice - Loggi, Elisabetta; Gitto, Stefano; Galli, Silvia; Minichiello, Mario; Conti, Fabio; Grandini, Elena; Scuteri, Alessandra; Vitale, Giovanni; Di Donato, Roberto; Cursaro, Carmela; Furlini, Giuliano; Andreone, Pietro (Journal of clinical virology, 2017)
•Past HBV infection seems not to predispose to HBV reactivation during DAA.•HBsAg-positive subjects should be controlled during and after DAA treatment.•Screening for HBV and longitudinal monitoring in selected cases are mandatory. Hepatitis B (HBV) reactivation in chronic hepatitis C (CHC) patients treated with IFN-free direct acting antiviral (DAA) therapies has recently emerged as a potential risk. Given the potential burden of this issue, further data are needed to establish its actual clinical impact. The aim of the present study was to analyze the occurrence of HBV reactivation in a cohort of CHC patient treated with DAAs in routine clinical practice. Consecutive CHC patients with different genotypes, treated with DAA between January 2015 and January 2016 were included in the study. Subjects had been tested for HBsAg and anti-HBc antibodies before antiviral therapy. HBV-DNA levels were examined in anti-HBc positive patients at baseline and 24 weeks after the end of treatment. Post-treatment HBsAg determination was performed in case of HBV-DNA positivity. Serum anti-HBs kinetics was analysed in anti-HBs and anti-HBc positive subjects. A cohort of 137 consecutive HCV patients treated with IFN-free regimens in routine clinical practice was evaluated. From this cohort, plasma samples of 44 subjects with positive serology for HBV (anti-HBc positive) were tested for HBV-DNA levels at baseline and 24 weeks after the end of treatment. Two of them were HBsAg-positive, while the others had signs of a past HBV exposure (HBsAg-negative±HBsAb-positive). No reactivation was found in HBcAb-positive and HBsAg-negative subjects. In the two HBsAg-positive, one experienced an increase in HBV-DNA levels of ≥2 log10 IU/mL during treatment. However, the reactivation was without clinical impact and, most important, was followed by HBsAg loss. Based on our experience, a past HBV infection seems not to be a condition predisposing to HBV reactivation. On the contrary, in HBsAg-positive subjects not in suppressive treatment with nucleos(t)ide analogs, regular monitoring of HBV-DNA during and after DAA treatment should be considered.